2022
DOI: 10.1038/s41598-022-06029-6
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported symptom study of COVID-19 chemosensory dysfunction in Malaysia

Abstract: Alterations in the three chemosensory modalities—smell, taste, and chemesthesis—have been implicated in Coronavirus Disease 2019 (COVID-19), yet emerging data suggest a wide geographic and ethnic variation in the prevalence of these symptoms. Studies on chemosensory disorders in COVID-19 have predominantly focused on Caucasian populations whereas Asians remain understudied. We conducted a nationwide, multicentre cross-sectional study using an online questionnaire on a cohort of RT-PCR-confirmed adult COVID-19 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Also, we found that the recognition of smells does not decrease proportionately for all fragrances because many study participants found it difficult to recognize the smell of chocolate. However, more scientific studies in this direction would provide more insight into this topic because several other studies found the mechanisms of olfactory disturbances to be either central or peripheral [ 6 , 16 , 25 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, we found that the recognition of smells does not decrease proportionately for all fragrances because many study participants found it difficult to recognize the smell of chocolate. However, more scientific studies in this direction would provide more insight into this topic because several other studies found the mechanisms of olfactory disturbances to be either central or peripheral [ 6 , 16 , 25 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated the variation in taste perception for all four main flavors based on evidence suggesting that the taste disturbances can be flavor-dependent [ 6 , 51 ]. Our study results also indicate that the COVID-19-associated decline in taste sensation and perception is not uniform in all flavor profiles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been speculations that GD was merely a side effect to OD, while other reports show a high prevalence and a distinct pathogenesis [ 8 10 ]. The pathogenesis for OD in COVID-19 is unknown, but it differs from other respiratory infections by being independent of nasal congestion [ 11 , 12 ]. Instead, local inflammation caused primarily by the binding of SARS-CoV-2 virus to the ACE-2 and TMPRSS2 receptors in the sustentacular (non-neural) cells of the olfactory epithelium seems crucial [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%